Association Between Vegetation Density and Standing Water Around Houses with Malaria Incidence in North Morowali Regency Indonesia - Puput Prasetiawan; Erwin Azizi Jayadipraja; Ridwan Adi Surya (Waluya The International Science of Health Journal, 2026)
Introduction: The increasing number of cases in the last 5 years is closely related to environmental characteristics, both physical, biological, and socio-cultural. The physical environment related to the presence of breeding places for Anopheles mosquitoes as malaria vectors has been shown to be closely related to the incidence of malaria cases in North Morowali. This study aims to Association Between Vegetation Density and Standing Water Around House with Malaria Incidence in North Morowali Regency, Indonesia. Method: This study is a quantitative study with a cross-sectional approach. The population was all 150 individuals suspected of having malaria who underwent Rapid Diagnostic Testing, and a sample size of 60 individuals. Purposive sampling was used to determine the sample and multiple logistic regression was used to obtain a model of the independent variables. Result: Statistically, these two groups are significant (p value < 0.05), meaning there is a significant relationship between trees/bushes around the house and (p value < 0.05), meaning there is a significant relationship between gutters/ditches/ponds around the house and the incidence of malaria cases.    Conclusion: There is a significant relationship between trees or dense bushes around the house and ditches or gutters that become places for stagnant water around the house with the incidence of malaria.